Distinguishing between bacterial and aseptic meningitis in children: European comparison of two clinical decision rules - Dubos, Francois; Korczowski, Bartosz; Aygun, Denizmen A.; Martinot, Alain; Prat, Cristina; Galetto-Lacour, Annick; Chalumeau, Martin (Bmj Publishing Group, 2010)
Background Clinical decision rules (CDRs) could be helpful to safely distinguish between bacterial and aseptic meningitis (AM). Objective To compare the performance of two of these CDRs for children: the Bacterial Meningitis Score (BMS) and the Meningitest. Design Secondary analysis of retrospective multicentre hospital-based cohort study. Setting Six paediatric emergency or intensive care units of tertiary care centres in five European countries. Patients Consecutive children aged 29 days to 18 years presenting with acute meningitis and procalcitonin (PCT) measurement. Intervention None. Main outcome measures The sensitivity and specificity of the BMS (start antibiotics in case of seizure, positive cerebrospinal fluid (CSF) Gram staining, blood neutrophil count >= 10 x10(9)/l, CSF protein level >= 80 mg/dl or CSF neutrophil count >= 1000 x10(6)/l) and the Meningitest (start antibiotics in case of seizure, purpura, toxic appearance, PCT level >= 0.5 ng/ml, positive CSF Gram staining or CSF protein level >= 50 mg/dl) were compared using a McNemar test. Results 198 patients (mean age 4.8 years) from six centres in five European countries were included; 96 had bacterial meningitis. The BMS and Meningitest both showed 100% sensitivity (95% CI 96% to 100%). The BMS had a significantly higher specificity (52%, 95% CI 42% to 62% vs 36%, 95% CI 27% to 46%; p<10(-8)). Conclusion The Meningitest and the BMS were both 100% sensitive. This result provides level II evidence for the sensitivity of both rules, which can be used cautiously. However, use of the BMS could safely avoid significantly more unnecessary antibiotic treatments for children with AM than can the Meningitest in this population.
Keywords: Cerebrospinal-Fluid Pleocytosis; Serum Procalcitonin; Markers; Sepsis; Level